2022
DOI: 10.3389/fonc.2022.903806
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Proteomics Analysis of Recurrent Low-Grade Serous Ovarian Carcinoma and Associated Brain Metastases

Abstract: Between 2% and 6% of epithelial ovarian cancer (EOC) patients develop brain metastases (brain mets), which are incurable and invariably result in death. This poor outcome is associated with a lack of established guidelines for the detection and treatment of brain mets in EOC patients. In this study, we characterize an unusual case of low-grade serous ovarian carcinoma (LGSOC) that metastasized to the brain. Using a spatially oriented single-cell proteomics platform, we compared sequential biopsies of a primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Cancer metastasis involves a number of dysregulated proteins and pathways (Weiss et al, 2022). Pejovic et al (2022) revealed various targetable carcinogenic pathways and immunosuppressive mechanisms that potentially determined brain metastases of epithelial ovarian cancer via a spatially oriented single‐cell proteomics platform. Notably, the spatially oriented single‐cell proteomics platform also uncovered that in the early stage of brain metastasis, the specific cell subtype has already emerged in the primary tumor.…”
Section: Applications Of Single‐cell Proteomics Analysis In Identifyi...mentioning
confidence: 99%
“…Cancer metastasis involves a number of dysregulated proteins and pathways (Weiss et al, 2022). Pejovic et al (2022) revealed various targetable carcinogenic pathways and immunosuppressive mechanisms that potentially determined brain metastases of epithelial ovarian cancer via a spatially oriented single‐cell proteomics platform. Notably, the spatially oriented single‐cell proteomics platform also uncovered that in the early stage of brain metastasis, the specific cell subtype has already emerged in the primary tumor.…”
Section: Applications Of Single‐cell Proteomics Analysis In Identifyi...mentioning
confidence: 99%